2017
DOI: 10.1093/ijnp/pyx051
|View full text |Cite
|
Sign up to set email alerts
|

Fenfluramine Reduces [11C]Cimbi-36 Binding to the 5-HT2A Receptor in the Nonhuman Primate Brain

Abstract: Background[11C]Cimbi-36 is a serotonin 2A receptor agonist positron emission tomography radioligand that has recently been examined in humans. The binding of agonist radioligand is expected to be more sensitive to endogenous neurotransmitter concentrations than antagonist radioligands. In the current study, we compared the effect of serotonin releaser fenfluramine on the binding of [11C]Cimbi-36, [11C]MDL 100907 (a serotonin 2A receptor antagonist radioligand), and [11C]AZ10419369 (a serotonin 1B receptor part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…Imaging of the 5-HT 2A R subtype is well established through antagonist tracers such as 18 F-seperone and 18 Faltanserine, with differences in receptor density identified in patients with obsessive-compulsive disorder [252], Tourette's syndrome [253], schizophrenia [254], and AD [255]. However, while able to report on receptor density, 5-HT 2A antagonist tracers are unable to distinguish between the high-and low-affinity states of 5-HT 2A and are relatively insensitive to endogenous neurotransmitter concentration [256,257]. As such abnormalities related to the 5-HT 2A high/low-affinity ratio or serotonin levels are unable to be identified using these tracers.…”
Section: Serotonin 5-ht 2 Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging of the 5-HT 2A R subtype is well established through antagonist tracers such as 18 F-seperone and 18 Faltanserine, with differences in receptor density identified in patients with obsessive-compulsive disorder [252], Tourette's syndrome [253], schizophrenia [254], and AD [255]. However, while able to report on receptor density, 5-HT 2A antagonist tracers are unable to distinguish between the high-and low-affinity states of 5-HT 2A and are relatively insensitive to endogenous neurotransmitter concentration [256,257]. As such abnormalities related to the 5-HT 2A high/low-affinity ratio or serotonin levels are unable to be identified using these tracers.…”
Section: Serotonin 5-ht 2 Rmentioning
confidence: 99%
“…In both human and NHP blocking, studies with 5-HT 2 R antagonist ketanserin (non-selective between 5-HT 2 subcategories A-C) showed significant reduction across the brain (Table 3) [103,104]. Pre-clinical studies have shown a significant response to pharmacologically increased and decreased levels of serotonin in vivo in NHP and rodents respectively showing the potential sensitivity of 11 C-Cimbi-36 to endogenous neurotransmitter concentration [257,259].…”
Section: Selectivity Data For 11 C-cimbi-36mentioning
confidence: 99%
“…Competitive binding assay from the Psychoactive Drug Screening Program (PDSP) of the National Institute of Mental Health (NIMH) shows that CIMBI-5 has equivalent affinity to 5-HT2BR and a threefold higher affinity to 5-HT2CR than to 5-HT2AR and did not have significant affinity for various other brain targets (24). Recently, [ 11 C]CIMBI-36 (Ki = 0.5 nM, Emax = 87%), the bromo-analogue of CIMBI-5, has been reported to have comparable specific to non-specific binding ratio as of [ 11 C]CIMBI-5 in pig and nonhuman primates; including receptor occupancy in pig brain and fenfluramine induced endogenous changes in monkeys (28)(29)(30)(31). Subsequently, [ 11 C]CIMBI-36 has been studied in human and thus it is so far the only 5-HT2AR agonist PET tracer studied in human (32).…”
Section: C]mdl100907mentioning
confidence: 99%
“…By contrast, agonist tracers should only bind to the active receptor pool and may thus provide additional information regarding neurotransmission . In this respect, agonists should be more sensitive to endogenous serotonin, and as a consequence agonists could serve as a tool to quantify endogenous serotonin concentrations within the synaptic cleft . Furthermore, agonist tracers should provide a better estimate of receptor occupancy levels of receptor activating therapeutic drugs .…”
Section: Introductionmentioning
confidence: 99%
“…23 In this respect, agonists should be more sensitive to endogenous serotonin, and as a consequence agonists could serve as a tool to quantify endogenous serotonin concentrations within the synaptic cleft. 24,25 Furthermore, agonist tracers should provide a better estimate of receptor occupancy levels of receptor activating therapeutic drugs. 26 Access to a 5-HT 2A R agonist PET tracer could provide insights into therapeutic mechanism of action, the effects on neurobiology and potentially help determine effective doses of similar drugs.…”
Section: Introductionmentioning
confidence: 99%